Effect of Work Environment and Work Motivation on Employee Performance at NTB Province Hospitals - Warosatul Hayani; Nurul Asfiah; R Iqbal Robbie (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This research examines the impact of the work environment and work motivation on employee performance. The study was conducted at NTB Provincial Hospital. The sampling technique uses proportional random sampling with a sample number of 86 employees. Using a quantitative approach. The data collection techniques in the study used questionnaires and interviews. The data analysis technique used in the study is Statistical Product and Service Solutions (SPSS). The results showed that there was a positive and significant influence between the work environment on employee performance. Work motivation has a positive and significant effect on employee performance, and the work environment and work motivation together have a positive and significant effect on employee performance.